Pengaruh Work Life Balance, Self-Efficacy, dan Komitmen Organisasional Terhadap Burnout pada Mahasiswa yang Bekerja [The Influence of Work Life Balance, Self-Efficacy, and Organizational Commitment on Burnout in Working Students] - Winata, Brigitta Liberty; Nurhasanah, Nina (Universitas Pelita Harapan, 2022)
This study aims to examine and analyze the effect of Work Life Balance, Self-Efficacy and Organizational Commitment on Burnout in working students. The research approach used in this research is quantitative research. The method used is a survey method by distributing questionnaires to Parallel Students of the Faculty of Economics and Business, Esa Unggul University, Kebon Jeruk. The questionnaires collected were 119 respondents, the data was then processed by the multiple linear regression method. The results of data analysis carried out with the help of SPSS 26 software for Windows. From the results of the study, the Work Life Balance variable has a significance value of 0.000 <0.05 with an Unstandardized Beta value of 0.582 which means that Work Life Balance has a positive influence on Burnout in working students. The Self-Efficacy variable (X2) has a significance value of 0.009 <0.05 with an Unstandardized Beta value of -0.257, meaning that the Self-Efficacy variable has a negative effect on Burnout in working students. The Organizational Commitment variable (X3) has a significance value of 0.878 with an Unstandardized Beta value of -0.017, meaning that the Organizational Commitment variable has a negative effect on Burnout. From the F test table, the F test value is 22.831 with a significant value of 0.000 <0.05. These results mean that there is a simultaneous influence of the three variables Work Life Balance, Self-Efficacy, and Organizational Commitment on Burnout in working students.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh Work Life Balance, Self-Efficacy dan Komitmen Organisasional terhadap Burnout pada mahasiswa yang bekerja. Pendekatan riset yang digunakan dalam penelitian ini adalah penelitian kuantitatif. Metode yang digunakan metode survey dengan cara menyebarkan kuesioner kepada Mahasiswa Paralel Fakultas Ekonomi dan Bisnis Universitas Esa Unggul, Kebon Jeruk. Kuesioner yang terkumpul sebanyak 119 responden, data tersebut kemudian diolah dengan metode regresi linear berganda. Hasil analisis data yang dilakukan dengan bantuan software SPSS 26 for Windows. Dari hasil penelitian, variabel Work Life Balance memiliki nilai signifikasi 0,000 < 0,05 dengan nilai Unstandardized Beta sebesar 0,582 yang dapat diartikan Work Life Balance memiliki pengaruh positif terhadap Burnout pada mahasiswa yang bekerja. Pada variabel Self-Efficacy (X2) memiliki nilai signifikasi 0,009 < 0,05 dengan nilai Unstandardized Beta sebesar -0,257, artinya variabel Self-Efficacy berpengaruh negatif terhadap Burnout pada mahasiswa yang bekerja. Pada variabel Komitmen Organisasional (X3) memiliki nilai signifikasi 0,878 dengan nilai Unstandardized Beta sebesar -0,017, artinya variabel Komitmen Organisasional berpengaruh negatif terhadap Burnout. Dari tabel Uji F didapat nilai uji F sebesar 22.831 dengan nilai signifikan 0.000 < 0.05. Hasil tersebut mengartikan bahwa terdapat pengaruh secara simultan ketiga variabel Work Life Balance, Self-Efficacy, dan Komitmen Organisasional terhadap Burnout pada mahasiswa yang bekerja.